Bullying victimization in schools in the United Arab Emirates: a cross-sectional study - Al-Ketbi, Alfan; Elkonaisi, Ismail; Abdullahi, Aminu S; Elbarazi, Iffat; Hamada, Bayan Abu; Grivna, Michal (BMC public health, 2024)
BACKGROUND: Despite the implementation of antibullying policies, schools in the United Arab Emirates (UAE) witnessed an increase in bullying prevalence. The aim of our study was to assess bullying victimization in schools in the UAE, types of bullying, and factors and outcomes related to bullying behavior. METHODS: A cross-sectional survey was conducted in randomly selected private and public schools in Al Ain City. A structured, self-administered questionnaire was used to collect data from students in grades 6-8 (Ages 10-15). We adapted the US CDC 'Bully Survey' for cultural relevance in the UAE through feedback from focus group meetings with teachers. Data analysis, conducted using R software, involved stratified analysis by school type and utilized Chi-Squared and Fisher's exact tests to identify factors associated with school bullying. RESULTS: The study sample consisted of 723 students of whom 68% were males, and 58% were Emirati nationals. The overall prevalence of bullying victimization in schools was 37%, with 40% in private schools and 35% in public schools. Cyberbullying was more prevalent in private schools (37%). Physical bullying was reported by 20% and verbal bullying by 12%, with a higher prevalence of physical bullying in private schools (24%) and among males (23%). The study's findings showed significant emotional and academic impacts of bullying, including feelings of sadness and learning difficulties, contributing to a rise in school absenteeism. CONCLUSIONS: The study reveals widespread bullying victimization in UAE schools, mainly in classrooms, with group exclusion and verbal abuse as key forms. It underscores bullying's psychological impact and the greater awareness of parents compared to teachers. The effective intervention strategies should not only involve students, teachers, and school staff, but also actively engage parents by fostering stronger communication channels between schools and families, and providing parents with resources and training to recognize and address bullying. These strategies should aim to create a cohesive network involving the entire school community, thus fostering a safer and more inclusive environment for students. The findings stress the need for inclusive antibullying programs involving the entire school community to foster a safer environment.
Keywords: Students; United Arab Emirates; průzkumy a dotazníky; Female; Prevalence; dítě; šikana; Spojené arabské emiráty; ženské pohlaví; průřezové studie; Surveys and Questionnaires; Adolescent; lidé; Bullying; školy; Schools; prevalence; Cross-Sectional Studies; Male; Child; studenti; mužské pohlaví; Crime Victims; oběti zločinu; mladiství; Humans